(untitled) (Eurasian Journal of Engineering and Technology, 2023)
In this article, we will discuss the functions of embedding algorithms for generating and verifying EDS in a cryptographic information security tool. Electronic Data Signatures (EDS) are crucial components of modern cryptographic information security tools. They provide authentication, integrity, and non-repudiation of electronic data, ensuring that the data has not been tampered with during transmission or storage. EDS are generated using a combination of hashing algorithms and digital signatures, which are then embedded into the electronic data.